Bilingualism in the family and child well-being: A scoping review. (October 2020) - Müller, Lisa-Maria; Howard, Katie; Wilson, Elspeth; Gibson, Jenny; Katsos, Napoleon
Aims and objectives: The aim of this scoping review is to investigate the association between bilingualism in the family and child subjective well-being, by reviewing the literature to identify key themes to date and remaining questions for future research. Methodology: Scopus, Web of Knowledge, ERIC, Psych Articles and PsychInfo were searched systematically between September and October 2018, and after title, abstract and full-text screening, 17 of the initial 1433 articles were included in this review. Data and analysis: Each study was coded for the discipline from which it emerged, the language combination studied, the measures of well-being and language proficiency it used, the geographical location of the study and the number of participants. Data on the link between bilingualism and well-being was extracted from each study. Findings and conclusion: Two main themes were identified: 'The effect of language proficiency on family relationships' and 'The acculturation of parents and children as mediated by language'. Across studies, there was significant heterogeneity in definition of concepts and a diverse range of measures employed. In addition, the studies identified suggest a positive link between minority language maintenance and child well-being, and a positive influence of bilingualism, rather than knowledge of only the home or the majority language. However, the directionality of these relationships will need to be investigated in future research. Originality: This is the first scoping review conducted systematically to explore the link between bilingualism in the family and child well-being internationally. It builds on previous work such as a narrative review which examined this association in the European context.